Predictors of caffeine consumption patterns in high school athletes - Eamonn M. O’Connell; Disa L. Hatfield; Amanda Stors; Steven A. Cohen (Journal of the International Society of Sports Nutrition)
Caffeine is the most widely used supplement by athletes. Caffeine’s benefits and its accessibility have led to increased consumption in young adults, despite limited research on athletic performance, efficacy, and possible side effects in this population. In addition, little research has been published examining the patterns of consumption in young athletes.Purpose The purpose of this study was to examine caffeine consumption and the factors that affect caffeine use in high school athletes.Methods Three hundred and ninety-four Rhode Island high school athletes (age: 16.8 ± 1.27 years) completed a cross-sectional online survey to assess caffeine consumption. A multivariate logistic regression analysis and binary logistic regression were performed to characterize associations between use and nonuse and the independent variables of ethnicity, grade, sex, and sport played. 95% confidence intervals (CI) were calculated for all models. Statistical significance was set to p ≤ 0.05 for all analysis.Results Fifteen point five percent of the variance in caffeine use was related to ethnicity, grade, and sex(R2 = 0.155), with significant results for each variable. A majority of female athletes consumed caffeine (67.4%), compared to male athletes (37.8%) (p < 0.001). Athletes identifying as Caucasian reported significantly more caffeine use (55.9%), compared to athletes from underrepresented backgrounds (32.6%) (p < 0.001). Caffeine use was significantly different across grades, where 30.6% of 9th graders, 49.2% of 10th graders, 55.2% of 11th graders, and 49.2% of 12th graders reported caffeine use (p = 0.049). Coffee (51%) and energy drinks (43%) were the primary sources of caffeine consumption. Dance, cheerleading, and gymnastics participants were more than ten times as likely to consume caffeine compared to other sports (95% CI [2.28, 48.94], Exp (β) = 10.57).Conclusion Caffeine use in young athletes is related to factors including sex and ethnicity. Given the prevalence of use, young athletes, coaches, and parents/guardians should be educated on the risks and benefits of caffeine use. Future research should focus on the potential benefits of caffeine use to athletic performance verses possible side effects in this population.Supported by The Clean Competition Grant from the Rhode Island Foundation.